Հայկական պատմամշակութային ժառանգության քարտեզների ստեղծման հարցի շուրջ - Աթոյան, Ռուբեն; Խեչոյան, Արմեն («Նաիրի» հրատ.)
Historical and cultural maps are an integral part of many atlases and are published separately also. On a simple base map using traditional symbols, objects of archeology, architecture, culture, art etc. are usually displayed. It uses a perfectly simple and non-associative signs. Therefore, these maps are the only sources of information, without any artistic value. In the present paper we propose the creation of new types of maps on the basis of landscape imagery. This a new direction in cartography.
Keywords: Քարտեզագրություն; Պատմամշակութային ժառանգություն